(untitled) (LACCEI, 2024)
The research design was carried out with the objective of determining the influence of residence time and pH on the reduction of silver by the biopolymerization of water from the Rio Grande. The study was developed with the realization of silver contents subjected to different residence times (40, 80, 120 minutes) and different pH values (2, 4, 6), assuming an initial silver concentration of 14.01 ppm. The study concluded its result with a reduction of silver (initial concentration: 14.01 ppm) at 40 minutes and 2 pH was 49.2% (7.12 ppm of Ag) and as the residence time and pH increase, the reduction of silver increased, obtaining a reduction of 96.3 % (0.52 ppm of Ag) with a parameter of 80 min and pH of 4. The results are verified by an analysis of variance of 95%.